Which impact of tumor density variations on absorbed dose in external radiotherapy. (September 2016) - Beilla, Sara; Chauveau, Nicolas; Laprie, Anne; Bardiès, Manuel; Franceries, Xavier
Abstract : Introduction: Dosimetry in external radiotherapy is based on tomodensitometry images that are required to be previously calibrated and assume that the electron density is comparable to the mass density. In Magnetic Resonance Imaging, and in particular diffusion sequence, significant heterogeneities have been shown. These heterogeneities result in density variations within the tumor, e.g. glioblastomas. Purpose: The aim of this study is to evaluate slight influence of mass density variations within the tumor via a dosimetric study. This can then be used to quantify the impact of those variations on modifications of dose 3D distribution. Materials and methods: This study is devoted to dosimetric calculations realization using TPS Eclipse AAA used in clinical. Treatments were carried out with 5 X-ray beams of 6 MeV, in optimized dynamic Intensity-Modulated-Radiotherapy. Mass density changes of GTV for the same treatment plans have been tested from 1.04 (default tumor density) to 1.8 g.cm −3 in steps of 0.1. Results: Dose-volume-histograms and profiles studies show a slight dose increase in surface GTV for the highest densities with significant changes isodose curves. Conversely, upon leaving the GTV, an under dosage of the tumor has been observed from a density variation from 1.04 to 1.2 g cm −3 . It was noted that density differences of 0.5 and 0.8 g cm −3 caused failure to respect the prescribed dose limits of ± 3% in brain volumes of 1.5 and 25 cm 3, respectively. Conclusion: Dose distributions variations were recorded by densities changes. From a change of 0.5 g/cm 3 within the tumor, dose prescriptions limits are not any more guarantees.